1997
DOI: 10.1097/00000542-199710000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-induced Delay in Gastric Emptying 

Abstract: The attenuation of morphine-induced delay in gastric emptying by methylnaltrexone suggests that the opioid effect is mediated outside the central nervous system. Methylnaltrexone may have the potential to decrease the side effects of opioid medications, which are mediated peripherally, while maintaining the central analgesia effect of the opioid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
98
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(102 citation statements)
references
References 27 publications
1
98
1
2
Order By: Relevance
“…Symptoms such as anorexia, nausea, vomiting, and dyspepsia are nonspecific and resemble many other conditions (186) and may just be associated with the presence of diabetes (181). Importantly, hyperglycemia, hypoglycemia, and acute changes in blood glucose are well documented to alter gastric emptying (182,187,188), as are some medications, especially opioids, other pain management agents, and glucagon-like peptide 1 receptor agonists (189,190). Therefore, all these factors known to affect gastric emptying should always be considered before a firm diagnosis is established.…”
Section: Gastrointestinal Neuropathiesmentioning
confidence: 99%
“…Symptoms such as anorexia, nausea, vomiting, and dyspepsia are nonspecific and resemble many other conditions (186) and may just be associated with the presence of diabetes (181). Importantly, hyperglycemia, hypoglycemia, and acute changes in blood glucose are well documented to alter gastric emptying (182,187,188), as are some medications, especially opioids, other pain management agents, and glucagon-like peptide 1 receptor agonists (189,190). Therefore, all these factors known to affect gastric emptying should always be considered before a firm diagnosis is established.…”
Section: Gastrointestinal Neuropathiesmentioning
confidence: 99%
“…[11][12][13] Further studies of methylnaltrexone for the treatment of constipation due to methadone use demonstrated rapid laxation response. [14][15][16] Two randomized, doubleblind, placebo-controlled studies of methylnaltrexone in 288 patients with advanced illness and OIC showed that methylnaltrexone rapidly induced laxation without compromising analgesia.…”
mentioning
confidence: 99%
“…Methylnaltrexone bromide is a selective peripherally acting μ-opioid receptor antagonist that has restricted ability to cross the blood-brain barrier. [12][13][14] It antagonizes the negative opioid-induced effects on the GI tract, such as delayed gastric emptying 15 and prolongation of oral-cecal transit time. 16 Methylnaltrexone is indicated for the treatment of OIC in adults with chronic noncancer pain and for the treatment of OIC in patients with advanced illness receiving palliative care who have had an inadequate response to laxative therapy.…”
mentioning
confidence: 99%